Drivers of self-employment: A multivariate decomposition analysis for the case of Germany - Michael Fritsch; Alexander Kritikos; Alina Sorgner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
We analyze the sources of the rise in the levels of self-employment in Germany since reunification by applying the non-linear Blinder-Oaxaca decomposition technique. This analysis is performed separately for East and West Germany in order to account for the East German recovery of entrepreneurship after 40 years of socialist regime. We find different results for self-employed people with employees and solo-entrepreneurs. The main factors determining changes in the level of self-employment are demographic developments, the shift toward service sector employment, and a higher share of population holding a tertiary degree. The analysis also suggests that changes in personal attitudes toward self-employment might be responsible for the particular increase of solo-entrepreneurship.
Keywords: L26; D22; 330; entrepreneurship; Germany; non-linear Blinder-Oaxaca decomposition technique; self-employment